High‐Performance Nonfullerene Polymer Solar Cells based on Imide‐Functionalized Wide‐Bandgap Polymers. Issue 21 (23rd March 2017) - Fan, Baobing; Zhang, Kai; Jiang, Xiao‐Fang; Ying, Lei; Huang, Fei; Cao, Yong
Abstract : High‐performance nonfullerene polymer solar cells (PSCs) are developed by integrating the nonfullerene electron‐accepting material 3, 9‐bis(2‐methylene‐(3‐(1, 1‐dicyanomethylene)‐indanone))‐5, 5, 11, 11‐tetrakis(4‐hexylphenyl)‐dithieno[2, 3‐ d :2′, 3′‐ d ′]‐s‐indaceno[1, 2‐ b :5, 6‐ b ′]dithiophne) (ITIC) with a wide‐bandgap electron‐donating polymer PTzBI or PTzBI‐DT, which consists of an imide functionalized benzotriazole (TzBI) building block. Detailed investigations reveal that the extension of conjugation can affect the optical and electronic properties, molecular aggregation properties, charge separation in the bulk‐heterojunction films, and thus the overall photovoltaic performances. Single‐junction PSCs based on PTzBI:ITIC and PTzBI‐DT:ITIC exhibit remarkable power conversion efficiencies (PCEs) of 10.24% and 9.43%, respectively. To our knowledge, these PCEs are the highest efficiency values obtained based on electron‐donating conjugated polymers consisting of imide‐functionalized electron‐withdrawing building blocks. Of particular interest is that the resulting device based on PTzBI exhibits remarkable PCE of 7% with the thickness of active layer of 300 nm, which is among the highest values of nonfullerene PSCs utilizing thick photoactive layer. Additionally, the device based on PTzBI:ITIC exhibits prominent stability, for which the PCE remains as 9.34% after thermal annealing at 130 °C for 120 min. These findings demonstrate the great promise of using this series of wide‐bandgap conjugated polymers as electron‐donating materials for high‐performance nonfullerene solar cells toward high‐throughput roll‐to‐roll processing technology. Abstract : High‐performance nonfullerene polymer solar cells with power conversion efficiencies of around 10% are achieved by integrating the wide‐bandgap polymers PTzBI or PTzBI‐DT with a nonfullerene acceptor ITIC. The extension of conjugation can affect the optical and electronic properties, molecular aggregation properties, and charge separation in the bulk‐heterojunction films, and thus the overall photovoltaic performances.